Homomorphisms to 3–Manifold Groups - Groves, Daniel; Hull, Michael; Liang, Hao (Geometric and functional analysis, 2025)
We prove foundational results about the set of homomorphisms from a finitely generated group to the collection of all fundamental groups of compact 3–manifolds and answer questions of Agol–Liu (J. Am. Math. Soc. 25(1):151–187, 2012 ) and Reid–Wang–Zhou (Acta Math. Sin. Engl. Ser. 18(1):157–172, 2002 ).